Addressing the toxic chemicals problem in plastics recycling - Bethanie Carney Almroth; Eric Carmona; Nnaemeka Chukwuone; Tridibesh Dey; Daniel Slunge; Thomas Backhaus; Therese Karlsson (Cambridge Prisms: Plastics)
Ongoing policy negotiations, such as the negotiations for a future global plastics treaty, include calls for increased recycling of plastics. However, before recycling of plastics can be considered a safe practice, the flaws in today’s systems must be addressed. Plastics contain a vast range of chemicals, including monomers, polymers, processing agents, fillers, antioxidants, plasticizers, pigments, microbiocides and stabilizers. The amounts and types of chemicals in plastics products vary, and there are little requirements for transparency and reporting. Additionally, they are inherently contaminated with reaction by-products and other nonintentionally added substances (NIASs). As the chemical composition of plastics wastes is largely unknown, and many plastics chemicals are hazardous, they therefore hinder safe recycling since recyclers are not able to exclude materials that contain hazardous chemicals. To address this problem, we suggest the following policy strategies: 1) improved reporting, transparency and traceability of chemicals in plastics throughout their full life cycle; 2) chemical simplification and group-based approaches to regulating hazardous chemicals; 3) chemical monitoring, testing and quality control; 4) economic incentives that follow the waste hierarchy; and 5) support for a just transition to protect people, including waste pickers, impacted throughout the plastics life cycle.